The Effectiveness of the Implementation of Occupational Health and Safety (OHS) in Indonesian Medical Personnel During the Covid-19 - Sunny Ummul Firdaus; Jamal Wiwoho; Muhamad Alief Hidayat (Universitas Kuningan, 2023)
This journal explains the effectiveness of legal protection for medical personnel, especially in implementing Occupational Safety and Health during the COVID-19 period. The number of COVID-19 cases that continue to develop in Indonesia certainly affects the implementation of OHS for medical personnel. Various problems also emerged in the first year of the spread of COVID-19, from medical personnel, instruments, and components supporting the implementation of OHS and the condition of COVID-19 in Indonesia. OHS accommodation for medical personnel has been listed in various laws and regulations in Indonesia. In this study, the author uses socio-legal legal research methods. The final result of this research is a study of the legal conditions of the laws and regulations governing the implementation of OHS for medical personnel in Indonesia, accompanied by various cases. This conclusion of the article provides the effectiveness of the implementation and compliance of das sollen and das sein law in Indonesia, especially regarding accommodating the implementation of Occupational Health and Safety (OHS) in accordance with legal regulations. With this issue, there is a need for synergy among the government, hospitals, healthcare workers, and relevant parties to ensure the implementation of OHS protection for medical personnel dealing with COVID-19 and the potential new mutated viruses emerging in Indonesia.